The liberty amendments : restoring the American republic - Levin, Mark R. (Mark Reed), 1957- (New York : Threshold Editions, 2013)
"The long-awaited new book on how to fix our broken government by the #1 New York Times bestselling author of Liberty and Tyranny and Ameritopia"--
"Mark Levin presents a proposal for new constitutional amendments to fix our broken country"--
Restoring the American Republic -- An Amendment to Establish Term Limits for Members of Congress -- An Amendment to Restore the Senate -- An Amendment to Establish Term Limits for Supreme Court Justices -- Two Amendments to Limit Federal Spending and Taxing -- An Amendment to Limit the Federal Bureaucracy -- An Amendment to Promote Free Enterprise -- An Amendment to Protect Private Property -- An Amendment to Establish How the States May Amend the Constitution -- An Amendment to Provide for States to Check Congress -- An Amend to Protect the Vote -- Epilogue: The Time for Action
Includes bibliographical references.
Keywords: Constitutional law -- United States; Law reform -- United States